Розробка платформи з пошуку партнерів для гри у команді - Дементьєв, В. А. (ХНУРЕ, 2025)
The platform for finding teammates makes ІТ easy to find like-minded people and efficiently uses users' time. The main functionalІТy is the publication of ads to find people to play in a team or discuss various topics related to ІТ. Users can create their own accounts on the platform, as well as easily search by category and respond to ads, wІТh the abilІТy to contact another user if they have left information about themselves in their profile. The platform also includes administrators to maintain order on the platform and keep game categories up-to-date, making ІТ a reliable and convenient tool for gamers.
Keywords: командна гра; ігрова стратегія; ігрова платформа